Travel Time Variability and Airport Accessibility - Paul Koster; Eric Kroes; Erik T. Verhoef (Tinbergen Institute, 2010)
This paper analyses the cost of access travel time variability for air travelers. Reliable access to airports is important since it is likely that the cost of missing a flight is high. First, the determinants of the preferred arrival times at airports are analyzed, including trip purpose, type of airport, flight characteristics, travel experience, type of check-in, need to check-in luggage. Second, the willingness to pay (WTP) for reduction in access travel time, early and late arrival time at the airport, and the probability to miss a flight is estimated using a stated choice experiment. The results indicate that the WTPs are relatively high, which is partially due to the low cost sensitivity of air travelers. Third, a model is developed to calculate the cost of variable travel times for air travelers going by car, taking into account travel time cost, scheduling cost and the cost of missing a flight. In this model, the value of reliability for air travelers is derived taking 'anticipating departure time choice' into account. Results of the numerical exercise show that the cost of access travel time variability for business travelers are between 3-36% of total access travel cost, and for non-business travelers between 3-30%. These numbers depend strongly on the time of the day.
Keywords: R41; L91; L93; D61; 330; value of reliability; scheduling; travel time variability; airport accessibility; airport choice; Transportzeit; Willingness to pay; Verkehrsmittelwahl; Zeitpräferenz; Flughafen; Theorie